Effect of high‐flow nasal cannula oxygen therapy on exercise tolerance in patients with idiopathic pulmonary fibrosis: A randomized crossover trial. Issue 2 (2nd November 2021) - Harada, Jumpei; Nagata, Kazuma; Morimoto, Takeshi; Iwata, Kentaro; Matsunashi, Atsushi; Sato, Yuki; Tachikawa, Ryo; Ishikawa, Akira; Tomii, Keisuke
Abstract: Background and objective: Exercise capacity in idiopathic pulmonary fibrosis (IPF) is limited by exercise‐induced hypoxaemia. This study aimed to examine the effect of high‐flow nasal cannula oxygen therapy (HFNC) on exercise tolerance in patients with IPF. Methods: We conducted a single‐centre, open‐label, randomized crossover trial to compare HFNC and Venturi mask (VM) therapy in terms of exercise tolerance. Patients underwent constant‐load symptom‐limited exercise testing at 80% peak work rate with HFNC or a VM in a randomized order. The settings were 60 L/min and a 50% fraction of inspired oxygen (FiO2 ) for HFNC and 12 L/min and 50% FiO2 for VM. The primary outcome was endurance time, and the secondary outcomes were heart rate (HR), percutaneous oxygen saturation (SpO2 ), dyspnoea and leg fatigue, as determined by the modified Borg Scale at the isotime and endpoint, and the level of comfort while using the devices. Results: Twenty‐four participants (75.0% men; age, median [interquartile range]: 77.5 [68.8–83.0] years) were enrolled. Compared with VM, HFNC significantly improved the endurance time (647.5 s [454.0–1014.8] vs. 577.5 s [338.0–861.5]), minimum SpO2 (96.0% [95.0–98.0] vs. 94.0% [92.8–96.0]) and leg fatigue at the isotime (3.0 [1.6–4.0] vs. 5.0 [3.0–6.3]) and endpoint (4.0 [2.8–5.0] vs. 5.0 [3.8–6.3]). Differences in maximum HR, dyspnoea at the isotime and endpoint and comfort were non‐significant between HFNC and VM therapy. Conclusion: HFNC increased exercise tolerance in patients with stable IPF experiencing exercise‐induced hypoxaemia. Abstract : We investigated the effect of high‐flow nasal cannula oxygen therapy (HFNC) on the exercise capacity of patients with idiopathic pulmonary fibrosis. HFNC exceeded the efficacy of conventional oxygen therapy and might be useful in pulmonary rehabilitation.